Shallow laccolithic emplacement of the Land's End and Tregonning granites, Cornwall, UK: Evidence from aureole field relations and P-T modeling of cordierite-anthophyllite hornfels - Pownall, J; Waters, D; Searle, M; Shail, R; Robb, L (2012)
The Land's End and Tregonning-Godolphin granites of the >250 km-long Permian Cornubian Batholith are heterogeneous medium- to coarse-grained peraluminous biotite-, tourmaline-, and lithium-mica granites traditionally thought to be emplaced as massive magmatic diapirs. Although S-type characteristics are dominant (quartz + biotite + muscovite + tourmaline ± topaz ± lithium-micas in the melt, numerous greisen and pegmatite veins, Sn-W mineralization), some characteristics of evolved I-type granites are also exhibited (hornblende-bearing enclaves, elevated εNd, Cu mineralization, batholithic dimensions). Here, we present an investigation focusing on the contact metamorphism and deformation of the aureole rocks adjacent to the Land's End and Tregonning granites as an approach to better determine the method of granite emplacement and the depth at which it occurred. New 1:5000-scale geological maps are presented for ~15 km of coastal exposure of the granites and their aureoles. We propose that the granites were emplaced non-diapirically by intrusion of sills that amalgamated to form a sheeted laccolith-type body. Granite contacts cleanly truncate all faults, folds, and cleavages generated during both Variscan convergence and subsequent latest Carboniferous-Early Permian (end-Variscan) extension, and it is likely that granite was emplaced during continuation of this extensional episode. There is evidence for stoping of the country rocks by an outward-migrated sill and dyke network, and uplift and doming of the host rocks can be partially attributed to laccolith inflation. Host meta-siltstones of the Devonian Mylor Slate Formation formed a contact aureole of cordierite + biotite + chlorite ± andalusite "spotted slates." Several interspersed pillow basalts and dolerites, previously affected by hydrothermal alteration, underwent isochemical contact metamorphism to form cordierite- and orthoamphibole-bearing hornfels, including cordierite-anthophyllite rocks that are present in Kenidjack cliff, NW Land's End aureole. THERMOCALC P-T modeling and pseudosection construction for these rocks in the large Na2O-CaOK 2O-FeO-MgO-Al2O3-SiO2-H 2O-TiO2-Fe2O3 (NCKFMASHTO) chemical system indicates contact metamorphism occurred at 1.5 ± 1.0 kbar and 615 ± 50 oC. This ultra-low pressure metamorphism equates to a likely emplacement depth of 5-6 km for the adjacent granite sheets. The Cornubian Batholith is highly composite and likely comprises an amalgamation of discrete shallow-seated sheeted laccoliths that are dyke-fed from a common lower-crustal/upper-mantle melt region to result in the batholith's mixed S-type/I-type character. © 2012 Geological Society of America.